Lipid-Lowering Treatment in Hypercholesterolemic Patients: The CEPHEUS Thailand Survey - Apichard Sukonthasarn (2018)
Background: Atherosclerotic cardiovascular disease (ASCVD) has become the leading cause of death and disability in Thailand. Low-density lipoprotein cholesterol is the major risk factor of this condition that can be intervened by means of lifestyle modification and pharmacologic treatment. Adequacy of hypercholesterolemia treatment with lipid lowering drugs in Thailand needed to be more clarified. The present study was conducted to determine low-density cholesterol goal attainment in Thai population at risk for developing ASCVD Material and Method: Twenty-seven physicians with their 909 hypercholesterolemic patients whose age of > 18 years, actively under pharmacologic treatment for at least three months with no dose adjustment for a minimum of six weeks from seven centers across Thailand were enrolled. Plasma glucose, total cholesterol, LDL cholesterol, HDL-cholesterol, and triglyceride levels were measured after overnight fast. Demographic and other relevant data including information on lipid lowering drug used were retrieved. Patients' awareness, knowledge on their management, compliance, and satisfaction were evaluated by questionnaire survey as well as physicians' use of guidelines, choice of management and goal setting, and their attitudes towards lipid management. Cardiovascular risk level and LDL goal were assessed by the updated 2004 NCEP-ATP III guidelines. Results: All patients had LDL goal of < 130 mg/dl with 86.1% needed LDL goal of < 100 mg/dL. Overall, 52.7% of the patients reached their LDL goal. The most prescribed treatment was statin monotherapy (82.7%). LDL goal attainment was inversely associated with LDL goal set by NCEP-ATP III according to the patients' risk profile, with only 16.7% of those who were in the very high risk group with LDL goal of < 70 mg/dL achieved their goal whereas 60.6% and 84.7% of those with high (LDL goal < 100 mg/dl) and moderately high-risk (LDL goal < 130 mg/dl) achieved their goal, respectively (p < 0.001). Other factors associated with less favorable LDL goal attainment were coronary heart disease, carotid artery disease, diabetes, 10-year risk of > 20%, and metabolic syndrome (p < 0.05 for all). Type of lipid lowering drug was not significantly associated with LDL goal attainment. Conclusion: LDL goal attainment was not achieved in a high proportion of Thai patients especially in those who had high to very high risk for developing cardiovascular disease. Despite availability of well-established treatment guideline and efficacious lipid lowering drugs, many patients still miss the opportunity to effectively control their lipid profile.